2009
DOI: 10.1111/j.1755-3768.2009.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of laser speckle flowgraphy in ocular blood flow research

Abstract: ABSTRACT.Laser speckle flowgraphy (LSFG) allows for the quantitative estimation of blood flow in the optic nerve head, choroid, retina and iris in vivo. It was developed to facilitate the non-contact analysis of ocular blood flow in living eyes, utilizing the laser speckle phenomenon. The technique uses a fundus camera, a diode laser, an image sensor, an infrared charge-coupled device (CCD) camera and a high-resolution digital CCD camera. Normalized blur (NB), an approximate reciprocal of speckle contrast, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
314
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 346 publications
(330 citation statements)
references
References 42 publications
1
314
0
1
Order By: Relevance
“…The determination of the LSFG from these images has been described in detail 11,12,18) . Briefly, the LSFG is obtained from a 21° section centered on the optic disc.…”
Section: Determination Of Optic Nerve Head Circulation By Pulse Wave mentioning
confidence: 99%
“…The determination of the LSFG from these images has been described in detail 11,12,18) . Briefly, the LSFG is obtained from a 21° section centered on the optic disc.…”
Section: Determination Of Optic Nerve Head Circulation By Pulse Wave mentioning
confidence: 99%
“…In the recent version of LSFG, a new parameter, mean blur rate (MBR), which is theoretically proportional to the square blur rate, is also commonly used as an idex of blood flow rate (Konishi, 2002). There have been many reports demonstrating the effects of various treatments on the ONH blood flow in humans using LSFG (Sugiyama et al, 2010). Some investigators have reported that ONH blood flow is autoregulated in normal eyes, but not in patients with POAG.…”
Section: Introductionmentioning
confidence: 99%
“…Laser Doppler flowmetry is predominantly sensitive to blood flow changes in the superficial layers of the ONH and gives very little information about the prelaminar and deeper regions of the ONH (Petrig et al, 1999). Laser speckle flowgraphy (LSFG) can detect capillary blood flow in the ONH, probably around the laminar region, and is suitable for monitoring the time-course of its change (Sugiyama et al, 2010). LSFG was develped to facilitate the non-contact analysis of ocular blood flow utilizing the laser speckle phenomenon (Tamaki et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…3 These unstable vascular abnormalities might also affect ocular blood flow, which can be assessed using color duplex imaging, laser speckle method, or Doppler flowmetry. 4,5 However, because the choroid receives approximately 95% of all ocular blood flow, changes in its structure could help to evaluate choroidal, thus ocular blood flow. 6 In several recent studies, optical coherence tomography (OCT) was introduced as an effective tool for evaluating choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%